Evidencing under-barrier phenomena in a Yb(iii) SMM: a joint luminescence/neutron diffraction/SQUID study. Issue 11 (25th September 2019) - Guégan, Frédéric; Jung, Julie; Le Guennic, Boris; Riobé, François; Maury, Olivier; Gillon, Béatrice; Jacquot, Jean-François; Guyot, Yannick; Morell, Christophe; Luneau, Dominique
Abstract : The synthesis, spectroscopic and magnetic characterisation and ab initio investigation of a new Yb based complex, [YbTp2 NO3 ], are reported and exploited to rationalise its field-induced SMM behaviour. Abstract : We report the synthesis, spectroscopic and magnetic characterisation and ab initio investigation of a new mononuclear ytterbium based complex, [YbTp2 NO3 ], and discuss the physical mechanisms underlying the slow relaxation of its magnetisation in a moderate static field and at low temperature.